Adaptation Problems of Foreign Students Studying in Secondary Education Institutions - Mustafa Soydam; Faruk Ateş (Journal of Educational Issues, 2024)
The principle of generality and equality, one of the fundamental principles of national education, states that educational institutions are open to all, regardless of religion, language, race or gender. In recent years, there has been an intense wave of migration from other countries to settle in Turkey. Especially in tourism cities, many people from different nationalities and cultures come and settle. As a result of the integration of these people from different cultures with each other and with local people, cities with a multicultural social structure are formed. With this project study, it is aimed to draw attention to the differences in the activities in the field of education and training in multicultural cities. For this purpose, Abdurrahman Alaattinoğlu Anatolian High School in Alanya district was selected as the study area. Foreign students at Abdurrahman Alaattinoğlu Anatolian High School were identified and a questionnaire was applied to students and parents. Oral and written interviews were conducted with the teachers and school administrators of these students. The data obtained were analyzed and interpreted, and the current situation was described. As a result of this study, it is hoped that a new perspective on multicultural education will be formed in administrators, teachers, parents of foreign students and Turkish families in the field of education. Because living conditions in the globalizing world make multicultural education compulsory.